2018
DOI: 10.1080/21645515.2018.1477458
|View full text |Cite
|
Sign up to set email alerts
|

The use of technology to promote vaccination: A social ecological model based framework

Abstract: Vaccinations are an important and effective cornerstone of preventive medical care. Growing technologic capabilities and use by both patients and providers present critical opportunities to leverage these tools to improve vaccination rates and public health. We propose the Social Ecological Model as a useful theoretical framework to identify areas in which technology has been or may be leveraged to target undervaccination across the individual, interpersonal, organizational, community, and society levels and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 126 publications
1
62
0
3
Order By: Relevance
“…5 This model has been extensively used to address health behaviors beyond individual characteristics. 6,7 According to prior research, individual-level risk factors associated with child immunization include the mother's employment status, educational level, and attitudes toward child immunization. 8,9 Interpersonal-level risk factors include the husband/partner's education and the number of children living in the household.…”
Section: Introductionmentioning
confidence: 99%
“…5 This model has been extensively used to address health behaviors beyond individual characteristics. 6,7 According to prior research, individual-level risk factors associated with child immunization include the mother's employment status, educational level, and attitudes toward child immunization. 8,9 Interpersonal-level risk factors include the husband/partner's education and the number of children living in the household.…”
Section: Introductionmentioning
confidence: 99%
“…Various social media platforms provide an online space for unregulated anti-vaccination and counter-factual information, such as lengthy lectures on YouTube by Polish doctors and academics [34,35] who are very sceptical about vaccination. As a result of the findings of this study, and recognizing the need for accurate, evidence-based information about vaccination on social media [36], NHS Health Scotland created an immunisation focused Twitter account in March 2019. Through this account, they have shared Polish-language Tweets and infographics to promote the influenza vaccine and have engaged with the Twitter accounts of several Polish community groups in Scotland, in an attempt to further reach the Polish community with accurate information about immunisations.…”
Section: Discussionmentioning
confidence: 99%
“…Through this account, they have shared Polish-language Tweets and infographics to promote the influenza vaccine and have engaged with the Twitter accounts of several Polish community groups in Scotland, in an attempt to further reach the Polish community with accurate information about immunisations. There is also a need to increase the presence of healthcare workers on social media [36]. Another approach to explore would be the use of talking-head videos with Polish healthcare workers in Scotland promoting the influenza vaccine, to be shared not only on NHS Twitter accounts but through the social media channels of schools and Polish community groups in Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly 44.6% of the respondents reported that their EMR system does not communicate with CAIR. A recent study from University of Columbia has shown that it is possible to automatically upload electronic daily immunization data into a citywide immunization registry in New York without additional workload for the staff (see ref 34) and bidirectional data exchange may improve immunization rates. 35 Interestingly, 27.0% of the responding providers in our study did not know whether their practice used CAIR.…”
Section: Discussionmentioning
confidence: 99%